소아 장중첩증에서 장절제술의 위험인자들에 대한 고찰 - 권대성(Dae Seong Kwon); 박찬일(Chan Il Park); 김병석(Byung Seok Kim); 문덕진(Duk Jin Moon); 박주섭(Ju Sup Park) (Annals of surgical treatment and research, 2002)
Purpose: Intussusception is one of the most common causes of childhood intestinal obstructions. Early diagnosis is essential to avoid treatment delays, which can increase morbidity and mortality. In this study, authors have tried to analyze the risk factors associated with intussusception in infants and children to establish an early diagnosis to prevent unwanted outcomes. Methods: We reviewed 44 cases involving operations for childhood intussusception from 1997 to 2001. These were divided into two groups and compared retrospectively using medical records. Group I included 34 cases of manual reduction (77.3%), and group II consisted of 10 cases of bowel resection (22.7%). Results: There were no significant differences in age, sex, and clinical symptoms between the 2 groups. The anatomic location of the intussusceptum, and fever seemed to vary, but this was of no statistical significance. Factors significantly contributing to increase in the rate of bowel resection were the duration of the symptoms (more than 48 hours), and the leukocyte count (more than 15,000/mm3). Conclusion: This study revealed that only the duration of symptom and the leukocyte count contributed to an increase in the rate of bowel resection. Further prospective studies would be needed to reveal more risk factors to accurately predict the prognosis of the disease. (J Korean Surg Soc 2002;63:63-68) KCI Citation Count: 0